2014
DOI: 10.1016/j.ijmm.2014.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Mucosa-associated Faecalibacterium prausnitzii and Escherichia coli co-abundance can distinguish Irritable Bowel Syndrome and Inflammatory Bowel Disease phenotypes

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
105
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 116 publications
(110 citation statements)
references
References 47 publications
3
105
0
2
Order By: Relevance
“…Patients with ileal CD harboured a higher number of E coli and its abundance was significantly associated with ileitis severity. More recently, Lopez-Siles et al 166 reported an association between higher numbers of E coli and a reduced interval to disease flare. These findings are in agreement with previous data reporting a correlation between increased levels of E coli outer membrane protein C (OmpC) and complicated CD with a greater need for surgery 167…”
Section: Aiec In Ibdmentioning
confidence: 99%
“…Patients with ileal CD harboured a higher number of E coli and its abundance was significantly associated with ileitis severity. More recently, Lopez-Siles et al 166 reported an association between higher numbers of E coli and a reduced interval to disease flare. These findings are in agreement with previous data reporting a correlation between increased levels of E coli outer membrane protein C (OmpC) and complicated CD with a greater need for surgery 167…”
Section: Aiec In Ibdmentioning
confidence: 99%
“…Mouse models revealed that Faecalibacterium prausnitzii has antiinflammatory properties and, in patients with CD, reductions in ileal F. prausnitzii abundance were associated with disease recurrence. 14 In patients with UC, studies have reported either no change 4,10,15 or lower 4,9,[16][17][18] abundance of F. prausnitzii. However, select patients with UC may carry increased amounts of this bacterium in the colonic mucosa.…”
Section: Introductionmentioning
confidence: 99%
“…The firmicute Faecalibacterium prausnitzii (Ruminococcaceae) is one of the three most abundant species, representing approximately 6 to 8% of the gut microbial community in healthy subjects, although it can reach up to 20% in some individuals (1,(4)(5)(6)(7)(8)(9)(10)(11). In contrast, depletion of F. prausnitzii has been reported to occur in several pathological disorders (for a review, see reference 12 and references therein), such as Crohn's disease (CD) (12-19), ulcerative colitis (UC) (11,14,15,17,(20)(21)(22)(23)(24)(25)(26), irritable bowel syndrome (IBS) of alternating type (27), colorectal cancer (CRC) (28, 29), and diabetes (30-32).Many studies have shown the potential role of F. prausnitzii in promoting gut health through the secretion of anti-inflammatory compounds, such as butyrate (16,(33)(34)(35)(36), and in reducing the severity of colitis induced in mice (16,37). Despite being a relatively abundant bacterium capable of regulating gut homeostasis (38, 39) and interacting in several host pathways (40), few studies have paid attention to the distribution of phylotypes within Faecalibacterium populations in the human gut.…”
mentioning
confidence: 99%
“…The firmicute Faecalibacterium prausnitzii (Ruminococcaceae) is one of the three most abundant species, representing approximately 6 to 8% of the gut microbial community in healthy subjects, although it can reach up to 20% in some individuals (1,(4)(5)(6)(7)(8)(9)(10)(11). In contrast, depletion of F. prausnitzii has been reported to occur in several pathological disorders (for a review, see reference 12 and references therein), such as Crohn's disease (CD) (12-19), ulcerative colitis (UC) (11,14,15,17,(20)(21)(22)(23)(24)(25)(26), irritable bowel syndrome (IBS) of alternating type (27), colorectal cancer (CRC) (28, 29), and diabetes (30-32).…”
mentioning
confidence: 99%